Self-Directed Learning: Paradigm Shift in Competency Based Medical Education – A Narrative Review - Ahmad, Ayesha; Nishad, Suman; Fatima, Bushra (International Journal of Human and Health Sciences (IJHHS), 2026)
Competency-Based Medical Education (CBME) in India has shifted medical training towards outcomes that emphasise self-directed lifelong learning as a core attribute of a competent physician. Self-Directed Learning (SDL) encourages learners to identify gaps in knowledge, access and evaluate relevant resources, reflect on their learning needs, and integrate knowledge into clinical practice. This paper aims to review the conceptual foundations, implementation strategies, benefits, and challenges of SDL within the CBME framework in undergraduate medical education in India. This narrative review is based on the National CBME guidelines of India, and published literature on SDL in medical education. Key themes included learner readiness, faculty roles in facilitating SDL, assessment methods aligned with SDL, and institutional strategies for integration. SDL improves learner engagement, critical thinking, and adaptability by promoting reflective practice and autonomous learning behaviours. CBME tools such as reflective portfolios, formative feedback, and workplace-based assessments provide opportunities for SDL; however, effective implementation is constrained by limited faculty training, traditional reliance on teacher-centred instruction, and variable student readiness for autonomous learning. SDL is integral to CBME and requires structured approach, faculty development, and institutional support to fulfil its potential in producing reflective, competent, and lifelong learners in medical practice. International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 78-81